Beyond the Scope of the Deal: Configuration of Technology Alliance Portfolios and the Introduction of Management Innovation. (17th March 2021) - Estrada, Isabel; Zhou, Haibo
Abstract: While firms invest in portfolios of technology alliances primarily seeking technological benefits (e.g. access to novel technological knowledge to develop product innovations), an adequate portfolio of technology alliances can also bring non‐technological benefits, such as access to novel managerial knowledge, which can result in management innovation. However, it remains unclear under what conditions technology alliance portfolios yield such benefits. Drawing from the literature on knowledge utilization from alliance portfolios, we examine how the configuration of a firm's technology alliance portfolio affects the likelihood of the firm introducing management innovation. Our panel data analyses of Spanish manufacturing firms for 2008–2016 reveal that a firm is more likely to introduce management innovation when its alliance portfolio shows diversity of partner types; however, this positive effect of diversity becomes less pronounced as the alliance portfolio becomes more oriented towards exploration (i.e. relatively greater presence of research‐focused partner types). Our study also provides recommendations for managers seeking to connect the technological and non‐technological spheres of innovation: a technological alliance portfolio that brings together diverse partner types while avoiding excessive presence of research‐focused partner types may offer greater opportunity for management innovation.